Analisis Dampak Putusan Mahkamah Konstitusi Terhadap Etika Penyelenggara Pemilu - Harid Fendra; Indah Adi Putri; Ria Ariany (Journal of Social and Policy Issues, 2022)
Law number 7 of 2017 has given a mandate to the Election Organizing Honorary Council (DKPP) as the body tasked with assessing and deciding the code of ethics for election organizers with a "Final and Binding" nature as stated in article 458 paragraph (13) meaning that there is no further effort other laws that can be taken, the implementation of the phrase "final and binding" is considered contrary to the Constitution because it can harm the constitutional rights of the organizers when the decision is wrong and cannot be corrected which can lead to disruption of the independence of the organizers as well as legal certainty and can disrupt the organizers' fair principle, then the judicial review was submitted to the Constitutional Court where the Constitutional Court decided that the phrase "Final and Binding" was contrary to the 1945 Constitution because DKPP was part of the general election organizing body and not other general judicial institutions. Continuing to the Administrative Court of course the decision has an impact on the ethics of the organizers, the formulation of the problem in this paper is how the impact of the decision of the Constitutional Court Number: 32/PUU/-XIX/2021 on the ethics of the organizers. This research is a descriptive qualitative research with a case study approach. The data used is secondary data, namely laws, decisions, regulations, books, journals and literature. The results of the study conclude that the decision of the Constitutional Court can have an impact on upholding the principles of Independent, Fair and Legal Certainty but also can not have any impact because 1. The nature of the decision of the Constitutional Court which is Declaratoir Constitutief 2. There is no norm in Law No. 7 of 2017 which regulates the obligation of the DKPP to implement the PTUN decision. 3. The ethical sanctions sentence in Law number 7 of 2017 is only directed at two organizing institutions, namely the KPU and Bawaslu.